Membranous glomerulonephritis in a patient with anti-u1 ribonucleoprotein (RNP) antibody-positive mixed connective tissue disease: A case report - Naoya Toriu; Junichi Hoshino; Eiko Hasegawa; Keiichi Sumida; Tatsuya Suwabe; Junichi Inenaga; Masahiro Kawada; Toshiharu Ueno; Koichi Kikuchi; Noriko Hayami; Akinari Sekine; Rikako Hiramatsu; et al. (Elsevier, 2018)
We report a 33-year-old Japanese man diagnosed with mixed connective tissue disease (MCTD) who developed nephrotic proteinuria. Both speckled antinuclear antibody (ANA) and anti-U1 ribonucleoprotein (RNP) antibody were positive, but anti-double-stranded DNA (dsDNA) antibody and anti-Smith (Sm) antibody were negative, while complement levels were normal. Renal biopsy revealed membranous glomerulonephritis (MGN) with diffuse thickening of the glomerular basement membrane (GBM) plus spike and bubble formation. Immunofluorescence demonstrated granular deposits of IgG and C3 along the GBM. Analysis of IgG subclasses showed predominant deposition of IgG1 and IgG4, unlike typical lupus nephritis in which there is predominant deposition of IgG1, IgG2, IgG3, and C1q. Electron microscopy identified numerous large electron-dense deposits (EDD) of various types in the subepithelial region of the GBM, but there were no EDD localized in the mesangium or subendothelium. Based on these findings, MGN was considered to be closely related to MCTD in this patient. Keywords: Membranous glomerulonephritis, Mixed connective tissue disease